Dylematy nauczyciela akademickiego kierującego seminarium magisterskim w ramach studiów tłumaczeniowych - Tomaszkiewicz, Teresa (Investigationes Linguisticae, 2019)
The following paper discusses the role of an MA seminar and an MA thesis in the process of education of professional translators who are more oriented toward gaining knowledge and skills instead of research activities. The Author, basing upon own experiences, aims to present dilemmas which academic teachers face while conducting such seminars as well as to explain how they can target students’ actions, so they can combine research activities with professional practice as part of a given educational path.